Factors affecting customer’s loyalty towards fast food restaurant in Subang Jaya / Shahril Anuar Jamar - Jamar, Shahril Anuar (Faculty of Business and Management, 2019)
This research objective is to examine the relationship between three hypothesis which is the relationship between service quality, food quality, price and ambience with customer loyalty towards fast food restaurant in Subang Jaya. For this purpose of study, the descriptive research was conducted. Convenience sampling has been utilised with 384 respondents as the sample size which 325 questionnaires were answered and collected from the respondents based on their consent and voluntary basis. The result indicates that the hypothesis shows both results with a positive relationship and negative relationship. For independent variables (price and ambience) shows positive relationship with the dependent variable (customer loyalty) while another two independent varibles (service quality and food quality) shows negative relationship with dependent variable (customer loyalty). All results and analysis has been evaluated by using SPSS (Statistical Package for Social Science during research been conducted.